The effectiveness of Tai Chi in improving depressive mood among young individuals aged 15–24 years: a systematic review and meta-analysis - Huang, Bozhen; Zhou, Meijiao; Jiang, Min; Song, Shanshan; Liu, Lei; Wang, Luyao; Wang, Liang; Jian, Yanhong; Wang, Ping; Yang, Tao; Shan, Xinjue; Liu, Xinqian (Frontiers in Public Health, 2025)
BackgroundDepression is a leading mental health concern among young individuals aged 15–24 years. Tai Chi, a low-cost, low-risk practice that has been shown to significantly alleviate depressive mood in the middle-aged and older adults, has not been rigorously evaluated in young individuals aged 15–24 years.MethodsRCTs evaluating Tai Chi therapy for young individuals aged 15–24 years with depressive mood were retrieved from several databases, including PubMed, Embase, Web of Science, Cochrane Library, CNKI, Wanfang Database, VIP Database, and CBM, covering the period from the database inception to May 18, 2025. The Cochrane Risk of Bias tool was employed to assess the bias risk in all included studies. Following a thorough screening process, data extraction, and coding, a meta-analysis was conducted using RevMan 5.2 and Stata 12.0.ResultsA total of 11 articles were included in the analysis, comprising 782 participants, with 434 in the Tai Chi intervention group and 348 in the control group. The meta-analysis results indicated that Tai Chi therapy effectively reduced depression scale scores in young individuals aged 15–24 years with depressive mood compared to the control group [SMD = −0.80, 95% CI (−1.14, −0.46), p < 0.001], but heterogeneity was high (I2 = 79.3%). Subgroup analyses showed that the intervention effect was optimal when the duration was 12 weeks [SMD = −1.11, 95% CI (−1.77, −0.45), p < 0.001]. The most significant intervention effect was observed when participants practiced Tai Chi for >3 h per week [SMD = −2.03, 95% CI (−3.63, −0.43), p < 0.001]. Sensitivity analyses indicated that the results of this study were robust and reliable. Publication bias was indicated by funnel plot asymmetry and Egger’s test (p = 0.042). The trim-and-fill analysis adjusted the pooled SMD from −0.80 (I2 = 79.30%) to −0.94 (I2 = 83.80%), indicating that the initial conclusion remained robust even in the presence of possible publication bias.ConclusionAs a non-pharmacological intervention, Tai Chi shows great promise in addressing depressive mood in young individuals aged 15–24 years within the field of mental health, warranting further research and promotion.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42024580026.